Pd/C-CaO-catalyzed alpha-alkylation and hydrodeoxygenation of an acetone-butanol-ethanol mixture for biogasoline synthesis - Huyen Thanh Vo; Yeo, Seung Mi; Dahnum, Deliana; Jae, Jungho; Hong, Chang Seop; Lee, Hyunjoo (ELSEVIER SCIENCE SA, 2017)
A solvent-free alpha-allcylation of acetone with butanol and ethanol was conducted using a mixture of Pd/C and CaO as heterogeneous catalysts. After reaction at 180 degrees C for 20 h, allcylated products, including C-5-C-11 ketones and alcohols, were obtained with a total yield of 78.1%. After this alpha-alkylation, consecutive hydrodeoxygenation at 270 degrees C for 20 h under H-2 at 500 psig yielded 74.7% C-5-C-11 alkanes based on the amount of acetone. The product could be used as a bio-gasoline. After alkylation, the catalyst was isolated and characterized using XRD, TGA, XPS, and TEM to elucidate the deactivation of the catalyst. The main reason was found to be decreased basicity of Ca species by conversion of CaO to CaCO3 during the reaction. The Pd/C particles were slightly agglomerated after alkylation, but still retained their catalytic activity during successive reuses for the alkylation reaction. In subsequent runs, the activity of the used catalyst could be recovered by adding a sufficient amount of CaO, or by decarboxylation of CaCO3 to CaO at 500 degrees C, under H-2. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: PRIMARY ALCOHOLS; CALCIUM-CARBONATE; KETONES; FERMENTATION; HYDROGENATION; CONVERSION; BIOFUEL